Factors of Youth Deviant Behavior Considering the Socio-Economic Development of Russian Regions - Bubnovskaia, Olesia; Yakubenko, Konstantin (Journal of Economic Sociology, 2024)
The article explores the factors influencing youth involvement in deviant behavior, taking into account the socio-economic development of various regions. The tendency towards deviant behaviors remains significant for societal development, causing harm to quality of life and well-being, while suppressing social and economic opportunities. Understanding the interdisciplinary and regional context may enhance the effectiveness of government programs aimed at scientifically based prevention and correction of youth deviant behavior. The study materials include research articles on deviance, official crime statistics, and socio-demographic issues from 2018 to 2023, as well as indicators of socio-economic development in Russian regions. These indicators encompass income levels, population statistics, economic inequality, quality of life, and commitment to a healthy lifestyle. Descriptive statistics, text analysis, structural equation modeling, correlation analysis, factor analysis, and regression analysis methods were employed for data processing and analysis. The research results revealed the complex economic causality of youth deviant behavior, which may arise from neglecting social and regional factors. While poverty is a significant contributor to deviance, its negative impact can be mitigated through involvement in social institutions and support networks. Conversely, crime as a form of deviance—particularly prevalent in regions with high economic prosperity— correlates with other forms of deviant behavior such as alcohol use. Notably, drug-related youth crimes are also high in these economically prosperous areas. In contrast, extremist and terrorist crimes are more common in regions with low socio-economic development where alcohol and smoking consumption is less prevalent. Overall, factors such as population size, quality of life, and commitment to a healthy lifestyle demonstrate higher statistical significance than economic inequality and income level as direct causes of deviant behavior among Russian youth.